Financial regulation in the aftermath of the great recession - Eroğlu, B. Barış (My University, 2019)
State intervention is a contentious subject from the beginning of the economic theories. Beginning from the 1970s or the rise of the finance-led accumulation regime, one of the main reflections of this discussion among thinkers has been the financial regulation. Throughout this period, financial crises that occurred several times provoked the discussion even more. In this paper, we examined three approaches, namely the French Regulation Approach, Ordoliberals and Minsky on the subject as a diverse bundle of point of views. Afterwards, the act of Dodd-Frank which is implemented in the aftermath of the Great Recession as a response in the US is analyzed in relation to the frameworks introduced. In other words, the suggestions of the different perspectives above are traced in the act. The effectiveness of the law is evaluated by using macroeconomic and financial indicators and the adequate and inadequate results are discussed accordingly. The advice of the financial regulation proponents followed in the act and appear to be working for a stable financial environment is pointed out whereas the missing core suggestions that seem to be still the reasons behind the fragility is analyzed too. Issues of transparency and the ’too big to fail’ problem along with the power imbalances shaping the relationship between the financial sector and the regulators are analyzed through the mediation of the Act. We found that, although the act has serious insufficiency areas, it is well designed and mostly in line with the suggestions of the scholars. However, the years following the declaration of the act became a battleground between the regulator and the financial incentives showing evidence on determinism of underlying power relations. We conclude that a proper regulation scheme cannot be implemented without a structural change in the accumulation regime.

Piyasalara devlet müdahalesi, ekonomik teorilerin başından itibaren tartışmalı bir konu olagelmiştir. 1970’lerden itibaren veya finans tabanlı birikim rejiminin ortaya çıkışı ile devlet müdahalesi tartışmalarının önemli konularından biri finansal regülasyon olmuştur. Bu dönem boyunca defalarca ortaya çıkan finansal krizler bu tartışmaları daha da ateşlemiştir. Bu metinde ekonomik sistem analizlerine bütünlükçü bakış açısına sahip olma ortak paydasında olan ve farklı perspektifler sunan Fransız Regülasyon Okulu, Ordoliberaller ve Minsky’nin konu üzerine düşüncelerini inceledik. Sonrasında, Büyük Durgunluğu takip eden süreçte ABD’de yürürlüğe giren Dodd-Frank yasasını, ele aldığımız düşünürlerin sunduğu bakış açıları üzerinden inceledik. Genel finansal indikatörler üzerinden yasanın etkinliğine baktık. Yasada uygulamaya geçen önerileri ve etkinliklerini analiz ettik. Yasanın önemli eksikleri olmasına rağmen, geniş çerçeveli ve etkin olduğunu gördük. Ancak regülasyon çerçevesinin politik belirlenimden kaçamayarak, gevşetildiğini gördük. Dolayısıyla Dodd-Frank yasasının, hem işler bir regülasyon çerçevesinin varlığının hem de birikim rejimine gömülü güç ilişkilerinden bağımsız bir etkin regülasyonun mümkün olmadığının önemli bir göstergesi olduğu sonucuna ulaştık.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Finansal regülasyon; Finansal krizler; Dodd-Frank yasası; Küresel ekonomik kriz; 2008 Krizi; Büyük durgunluk; Ordoliberaller; Financial regulation; Financial crisis; Dodd-Frank act; Great recession; Ordoliberals